First report of the fall armyworm, Spodoptera frugiperda (J E Smith) (Lepidoptera: Noctuidae), an alien invasive pest on maize in India - Sharanabasappa, S.D.; Kalleshwara Swamy, C.M.; Asokan, R.; Swamy, H.M.M.; Maruthi, M.S.; Pavithra, H.B.; Hegbe, K.; Navi, S.; Prabhu, S.T.; Goergen, Georg E. (2018)
The global agriculture often faces new threats from invasive alien insect pests, pathogens, weeds etc requiring immediate attention and co-operative action to manage the pestilence. In this regard, the fall armyworm (FAW), Spodoptera frugiperda is a notorious pestiferous insect with high dispersal ability, wide host range and high fecundity that make it one of the most severe economic pests. The FAW has been restricted to the Americas and recently in 2016 reported from various countries in Africa, posing a serious challenge of sustainability in Sub-Saharan African countries. Herewith we report the occurrence of the FAW on maize in various districts of Karnataka state, India. Identification of FAW has been carried out employing morphological and DNA barcoding. Phylogenetic analysis has revealed that FAW clustered with Florida (rice strain), Ghana, Nigeria, Uganda on maize. India predominantly being a tropical country favours high rate of multiplication round the year and its high pestiferous nature poses a formidable challenge to Indian agriculture warranting immediate action before it assumes a serious proportion.